PENGARUH PENGGUNAAN RAGI ROTI DAN IKAN RUCAH SEBAGAI PENGGANTI (NANOCHLOROPSIS SP.) DALAM KULTUR ROTIFER DI BPBL LOMBOK: The Effect Of Using Year Bread And Rucah Fish As An Replacement (Nanochloropsis Sp.) In Rotifer Culture In Lombok BPBL - Kaisar, Edo Rezal Yulian; Gede Sumahiradewi, Luh; Sukmaring Kalih, L.A.T.T.W.; Yoga Sativa, Denianto (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2023)
Rotifers are the main feed during the hatchery process in fisheries. However, rotifers rely heavily on Nannochloropsis as their natural feed. This research was conducted to find out alternative feeds for rotifers. This study used bread yeast, and trash fish as an alternative feed for eight days. The results showed that the growth of control treatment (Nannochloropsis) of 1,125 x 106 individuals.mL-1 with peak growth occurred on day V, bread yeast treatment by 1,215 x 106 individuals.mL-1 with peak growth occurred on day III, Trash Fish treatment by 0.885 x 106 individuals.mL-1 with peak growth occurred on day IV and a mixture of bread yeast and trash fish of 1,095 x 106 individuals.mL-1 with peak growth occurred on day IV